Evaluation of SARS-CoV-2 diagnostics and risk factors associated with SARS-CoV-2 infection in Zambia. (July 2022) - Tembo, John; Egbe, Nkongho Franklyn; Maluzi, Kwitaka; Mulonga, Kangwa; Chilufya, Moses; Kapata, Nathan; Mukonka, Victor; Simulundu, Edgar; Zumla, Alimuddin; Fwoloshi, Sombo; Mulenga, Lloyd; Pallerla, Srinivas Reddy; et al.
Abstract: Objectives: To conduct a diagnostic validation study of SARS-CoV-2 diagnostic kits. Methods: We compared SARS-CoV-2 diagnostic test results from 3 RT-PCR assays used by the Zambian government between November 2020 and February 2021 (Panther Fusion assay, Da An Gene's 2019-nCoV RNA kit and Maccura's PCR Kit) with the Altona RealStar RT-PCR kit which served as the gold standard. We also evaluated results from rapid antigen testing and whether comorbidities were linked with increased odds of infection. Results: We recruited 244 participants, 61% (149/244) were positive by at least 1 PCR assay. Da An Gene, Maccura, and Panther Fusion assays had sensitivities of 0.0% (95% confidence interval [CI] 0%–41%), 27.1% (95% CI 15%–42%), and 76% (95% CI 65%–85%), respectively, but specificity was low (<85% for all 3 assays). HIV and TB were not associated with SARS-CoV-2, whereas female sex (OR 0.5 [0.3–0.9], p = 0.026) and chronic pulmonary disease (0.1 [0.0–0.8], p = 0.031) were associated with lower odds of SARS-CoV-2 infection. Of 44 samples, 84% sequenced were Beta variant. Conclusions: The RT-PCR assays evaluated did not meet WHO recommended minimum sensitivity of 80%. Local diagnostic validation studies should be embedded within preparedness plans for future outbreaks to improve the public health response.